2022
DOI: 10.1371/journal.pone.0273427
|View full text |Cite
|
Sign up to set email alerts
|

Game statistics that discriminate winning and losing at the NBA level of basketball competition

Abstract: The purpose of the present study was to examine differences in game-related statistical parameters between National Basketball Association (NBA) regular and post-season competitive periods and to determine which variables have the greatest contribution in discriminating between winning and losing game outcomes. The data scraping technique was used to obtain publicly available NBA game-related statistics over a three-year span (2016–2019). The total number of games examined in the present investigation was 3933… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 17 publications
4
28
0
Order By: Relevance
“…Moreover, defensive rebounds emerged as a prominent performance parameter associated with securing the desired game outcome during the post-season competitive period (Garcia et al, 2013;Trninic et al, 2002). Similar observations were made in a recently conducted study where field goal percentage and defensive rebounds were found to be two key game-related statistics capable of discriminating between winning and losing game outcomes during both regular and post-season competitive periods at the National Basketball Association (NBA) level of basketball competition (Cabarkapa et al, 2022). Furthermore, it is interesting to note that besides superior scoring capabilities, NBA teams are likely to be more successful when all players, regardless of team status (i.e., starters or non-starters), commit themselves to passing the ball (Melnick, 2001).…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…Moreover, defensive rebounds emerged as a prominent performance parameter associated with securing the desired game outcome during the post-season competitive period (Garcia et al, 2013;Trninic et al, 2002). Similar observations were made in a recently conducted study where field goal percentage and defensive rebounds were found to be two key game-related statistics capable of discriminating between winning and losing game outcomes during both regular and post-season competitive periods at the National Basketball Association (NBA) level of basketball competition (Cabarkapa et al, 2022). Furthermore, it is interesting to note that besides superior scoring capabilities, NBA teams are likely to be more successful when all players, regardless of team status (i.e., starters or non-starters), commit themselves to passing the ball (Melnick, 2001).…”
Section: Introductionsupporting
confidence: 81%
“…Attempting free-throw shots is an uncontested scoring opportunity that can be advantageous in securing the winning game outcome (Cabarkapa et al, 2022;Conte et al, 2018;Csataljay et al, 2012). Therefore, combining a greater number of PF committed by the opposing team that results in more FTA creates an additional home-court advantage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be achieved by attempting free-throw, two-point, and three-point shots. The efficiency of the aforementioned shooting motions has been shown to be one of the key factors in securing the desired game outcome across various levels of basketball competitions [ 2 , 3 , 4 , 5 ]. Therefore, it is of critical importance that each player possesses elementary knowledge regarding the proper shooting form as well as what biomechanical adjustments are needed when increasing the shooting distance.…”
Section: Introductionmentioning
confidence: 99%
“…Basketball is an intermittent, and a complex game where shooting is one of the most important technical skills of the game (Zwierko et al, 2018;Li et al, 2021). More precisely, shooting efficiency is considered one of the crucial performance indicators due to the strong positive relationship between field goal shooting and winning the game (Ibáñez et al, 2009;Lorenzo et al, 2010;García et al, 2013;Cabarkapa et al, 2022b). However, shooting performance in a game can be determined by various endogenous and exogenous factors that disrupt its effectiveness.…”
Section: Introductionmentioning
confidence: 99%